Integrated network pharmacology and hepatic metabolomics to reveal the mechanism of Acanthopanax senticosus against major depressive disorder - Gu, Xinyi; Zhang, Guanying; Wang, Qixue; Song, Jing; Li, Ying; Xia, Chenyi; Zhang, Ting; Yang, Li; Sun, Jijia; Zhou, Mingmei (Frontiers in Cell and Developmental Biology, 2022)
Objective: Acanthopanax senticosus (Rupr.et Maxim.) Harms (ASH), a traditional herbal medicine widely known for its anti-fatigue and anti-stress effects, as well as tonifying qi, invigorating spleen and kidney, tranquilizing the mind. Recent evidence suggests that ASH has a therapeutic effect on major depressive disorder (MDD), but its mechanism of is still unclear. The current study aimed to investigate the effect of ASH on MDD and potential therapeutic mechanisms. Materials and Methods: Chemical compound-potential target-network was predicted based on network pharmacology. Simultaneously, chronic unpredictable mild stress (CUMS) model mice were orally administrated ASH with 3 dosages (400, 200, and 100 mg/kg) for 6 weeks, and hepatic metabolomics based on gas chromatography-mass spectrometry (GC-MS) was carried out to identify differential metabolites and related metabolic pathways. Next, the integrated analysis of metabolomics and network pharmacology were applied to find the key target. Finally, molecular docking technology was employed to define the combination of the key target and the corresponding compounds. Results: 13 metabolites and 4 related metabolic pathways were found in metabolomics analysis. From the combined analysis of network pharmacology and metabolomics, 6 targets (DAO, MAOA, MAOB, GAA, HK1 and PYGM) are the overlapping targets and 2 metabolic pathways (glycine, serine and threonine metabolism and starch and sucrose metabolism) are the most related pathways. Finally, DAO, MAOA, MAOB, GAA, HK1 and PYGM were verified bounding well to their corresponding compounds including isofraxidin, eleutheroside B1, eleutheroside C, quercetin, kaempferol and acacetin. Conclusions: These results demonstrate that the mechanism of ASH on MDD was related to the regulation of metabolism of several excitatory amino acids and carbohydrate, as well as the expression of DAO, MAOA, MAOB, GAA, HK1 and PYGM.